Effectiveness of a personal health coaching intervention (diabetescoach) in patients with type 2 diabetes: protocol for an open-label, pragmatic randomised controlled trial. Issue 6 (1st June 2022) - Hohberg, Vivien; Kreppke, Jan-Niklas; Kohl, Jan; Seelig, Eleonora; Zahner, Lukas; Streckmann, Fiona; Gerber, Markus; König, Daniel; Faude, Oliver
Abstract : Introduction: The widespread prevalence of type 2 diabetes (T2D) not only influences patients' daily lives but also has an economic impact on society. Increasing physical activity and a healthy diet can delay the progression of T2D. Although there are evidence-based recommendations on diet and physical activity, patients with T2D have difficulties implementing them. An appropriate lifestyle intervention can address this problem. Methods and analysis: This study is based on the need to develop an intervention that helps patients to establish behavioural changes in order to achieve glycaemic control. The intervention will be evaluated in a monocentric, open-label, pragmatic, two-arm randomised controlled trial with a sample ratio of 1:1 and a parallel design. This superiority study will be conducted in Switzerland. All enrolled patients (n=90) will receive the standard medical treatment for T2D. The intervention group will receive personal health coaching by telephone and access to a smartphone and web application for 1 year. The control group will receive access to the application for 1 year and a one-time written diet and exercise recommendation. The primary outcomes are objectively measured physical activity and glycated haemoglobin. Secondary outcomes are self-reported physical activity, nutrition, cognitive mediators of changes in sport-related behaviour, blood values, medication and nutritional supplements, anthropometric data, quality of life, neuropathy and cost-effectiveness. All outcomes will be measured at baseline, at 27 weeks after inclusion and at 54 weeks after inclusion. The recruitment of participants and the measurements will be completed after 2 years. Linear mixed-effects models will be applied for each outcome variable to analyse the intervention effects. Ethics and dissemination: This study was approved by the Ethics Committee North-western and Central Switzerland in February 2021 (ref: 2020-02755). All participants will be required to provide written informed consent. The results will be published in international peer-reviewed journals. Trial registration number: ISRCTN79457541 .